Case Report: Long-term response control in a patient with metastatic gastric squamous cell carcinoma treated with nivolumab and chemoradiotherapy - Lei, Yu-ying; Li, Li; Shi, Ya-bin; Han, Xiao-hui; Li, Yi-tong; Ren, Wen-jun; Sui, Ai-xia (Frontiers in Immunology, 2025)
Primary gastric squamous cell carcinoma (GSCC) is rare, typically associated with poor survival rates and unsatisfactory outcomes from conventional treatments including surgery, radiotherapy, and chemotherapy. It remains unclear whether nivolumab is as effective for GSCC as it is for gastric adenocarcinoma. Herein, we present the case of a 66-year-old man diagnosed with Epstein-Barr virus-positive metastatic GSCC, involving the liver, multiple lymph nodes, and invasion into the spleen, pancreatic body and tail, and splenic vein. The patient received nivolumab with oxaliplatin, leucovorin, and fluorouracil plus local radiotherapy as first-line treatment; nivolumab, paclitaxel polymer micelles, and carboplatin as the second-line treatment, and nivolumab and apatinib as the third-line treatment. The patient responded remarkably (survival period for 49 months) with manageable treatment toxicity. Genomic and immune characteristics were analyzed to understand the underlying disease mechanisms. In conclusion, integrated therapy (immunotherapy, chemotherapy, local radiotherapy, and anti-angiogenic therapy) may be the ideal treatment approach for patients with GSCC with multiple metastases; however, prospective studies are needed to verify its efficacy.